دور بطاقة الأداء المتوازن في تقييم الأداء المالي للمؤسسات الاقتصادية - بوطورة, فاطمة الزهراء; رقام, ليندة (المجلة الجزائرية للأمن والتنمية Algerian Review of Security and Developement, 2024)
تعتبر عملية قياس وتقييم الأداء في المؤسسة الاقتصادية من أهم آليات مراقبة التسيير واتخاذ القرارات الرشيدة بالمؤسسة، ونتيجة لقصور الأدوات التقليدية في قياس وتقييم أداء المؤسسات أدى بالكثير من الباحثين والمفكرين إلى تطوير أدوات قياس حديثة تتمكن من خلالها المؤسسات الاقتصادية من قياس وتقييم أدائها بشكل عام وأدائها المالي بشكل خاص، مثل أداة بطاقة الأداء المتوازن من خلال أربعة أبعاد رئيسية: البعد المالي، بعد العمليات الداخلية، بعد العملاء وبعد التعلم والنمو، وعليه فقد أوصت الدراسة بضرورة تحقيق التكامل والتنسيق بين مختلف مقاييس الأداء في المؤسسات وعدم تركيز نجاحها على المؤشرات المالية في تحديد الأهداف. The Process of measuring and evaluating performance in the economic institution is considered one of the most important mechanisms for monitoring the management and making rational decisions in the institution, and as a result of the lack of traditional tools in measuring and evaluating the performance of institutions, many researchers and intellectuals have led to the development of modern measurement tools through which economic institutions can measure and evaluate their overall performance and financial performance In particular, Such the balanced scorecard tool through four main dimensions : The financial dimension, after internal processes, after customers and after learning and growth. And therefore the study recommended the necessity of achieving integration and coordination between the various measures of performance in institutions and not focusing their success on financial indicators in setting goals and setting strategies.